Testing Times as Foreign Minister - Khan, Gohar Ayub 1937- (Islamabad Dost Publications, 2009)
Collection of author's speeches and statements as foreign minister of Pakistan.
Include Illustration
Keywords: Pakistan -- Diplomatic relations -- Khan, Gohar Ayub, 1937-